How Fast Should Trades Settle? - Khapko, Mariana; Zoican, Marius (Management Science, 2020)
Recent regulatory and industry initiatives aim to streamline post-trade infrastructures. Does faster settlement benefit markets? We build a model of intermediated trading with imperfectly competitive securities lending. Faster settlement benefits impatient traders but increases borrowing needs. We find that flexible failure-to-deliver penalties reduce this tension, disciplining security lender competition and allowing for real-time settlement. Optimal penalties resemble put options on the lending market: they protect traders against high settlement costs but do not eliminate failures to deliver. Mandating automatic security borrowing to prevent failures to deliver triggers a toxic settlement rat race to lock in low borrowing costs. This paper was accepted by Gustavo Manso, finance.